KINERJA PEGAWAI TERHADAP PENINGKATAN KUALITAS PELAYANAN PADA KUA KECAMATAAN SOMBA OPU KABUPATEN GOWA - Yani, Yani; Usman, Jaelan; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aimed 1) to find out how  the performance of employees at the Office of Religious Affairs, Somba Opu District, Gowa Regency, 2) to find out how good the quality of service at the Office of Religious Affairs, Somba Opu District, Gowa Regency and 3) to find out how the influence employee performance on quality services at the Office of Religious Affairs, Somba Opu District, Gowa Regency. The population and sample in this study amounted to 20 employees, data collection by questionnaire. Data analysis used descriptive analysis and simple linear regression analysis. The results showed that: 1) Employee performance was in good category with process indicators being the most prominent in shaping employee performance at the KUA Somba Opu Office, Gowa Regency, 2) Service quality was in good category with responsiveness indicators being the most prominent in forming service quality at the KUA Somba Opu Office, Gowa Regency, and 3) Employee performance had a positive and significant effect on service quality at the KUA Somba Opu Office, Gowa Regency.